Running injury prevention and performance enhancement: from the lab to the field - van Hooren, B. P. M. (2025)
This PhD thesis explored novel methods to prevent running injuries and enhance running performance. It consists of three parts. Part 1 Investigated muscle behavior and activation during different exercises and yielded novel insights regarding which strength training exercises may be best to prevent hamstring injuries and rehab after injury. Part 2 investigated the relationship between running technique and loading at common running injury locations (Achilles tendon, shin and knee), as well as the relationship between running technique and running efficiency. This yielded novel insights into treadmill vs. overground running, the impact of different running styles, speeds and slopes on loading at common running injury locations and the most efficient running technique. Part 3 developed and validated wearable sensors to quantify loading at common running injury locations in-field, and alter running technique, both to reduce injury risk and enhance running performance. Most importantly, this thesis showed that real-time feedback using the developed wearable device reduced the number of running injuries and therefore can increase sports participation.